Effectiveness of Clove Flower Extract (Syzygium Aromaticum L.) as Analgesic on Licking Time Reaction in Male Mice with Formalin Induction - Puspitasari, Vina; Wahjuni, Retno Sri; Saputro, Amung Logam; Hamid, Iwan Sahrial; Wibawati, Prima Ayu (Universitas Airlangga, 2021)
This research is about testing the effectiveness of clove flower extract (Syzygium aromaticum L.) as an analgesic against the beating time caused by formalin male mice. This research is experimental with the Complete Random Design formula producing four times repetition (N = 4) and divided into five treatment groups (t = 5). Data were analyzed using ANAVA factorial test then followed by Duncan test. All tests are carried out with Product Solutions and Service Statistics (SPSS). The results of research and statistical analysis prove that clove flower extract at a dose of 1% is an effective dose compared to other treatment groups, seen from the amount of time licking male mice which is smaller than other treatment groups. It can be concluded that the administration of clove flower extract has analgesic effectiveness against the reaction of male mice induced by formalin. The concentration of clove flower extract 1% is the most effective in reducing licking time.